Advanced glycosylation endproducts block the antiproliferative effect of nitric oxide. Role in the vascular and renal complications of diabetes mellitus. - Hogan, M; Cerami, A; Bucala, R (The Journal of Clinical Investigation, 1992)
Advanced glycosylation endproducts (AGEs) accumulate on long-lived tissue proteins such as basement membrane collagen and have been implicated in many of the long-term complications of diabetes mellitus. These products originate from glucose-derived Schiff base and Amadori products but undergo a series of complex rearrangement reactions to form ultimately protein-bound, fluorescent heterocycles. AGEs can react with and chemically inactivate nitric oxide (NO), a potent endothelial cell-derived vasodilator and antiproliferative factor. Since mesenchymal cell proliferation is an early and characteristic lesion of diabetic vasculopathy and glomerulopathy, we investigated the possibility that collagen-bound AGEs functionally inactivate the antiproliferative effect of NO. In model cell culture systems, AGEs were found to block the cytostatic effect of NO on aortic smooth muscle and renal mesangial cells. The inactivation of endothelial cell-derived NO by basement membrane AGEs may represent a common pathway in the development of the accelerated vascular and renal disease that accompany long-term diabetes mellitus.